Possibilities of Integration of Ferry Service in the Port of Koper - Igor Jakomin; Milan Pučko (Promet - Traffic&Transportation, 1970)
The Municipality authority of Koper and the company Portof Koper Ltd. have agreed that a part of the existing port infrastructurebe returned to the town again. The development planof the town foresees that the old town core be revitalisedthrough the northern bypass road again.The paper presents the possibility of the integration ofKoper in maritime passenger traffic, which represents a newpossibility for the cuffent and future tourist and economic development.The solution proposed enables fast inclusion of theport of Koper port in the ferry service without substantial investmentsin infrastructure.